Biochemical response to substrate reduction therapy versus enzyme replacement therapy in Gaucher disease type 1 patients. Issue 1 (December 2016) - Smid, Bouwien; Ferraz, Maria; Verhoek, Marri; Mirzaian, Mina; Wisse, Patrick; Overkleeft, Herman; Hollak, Carla; Aerts, Johannes
Abstract Background We retrospectively compared biochemical responses in type 1 Gaucher disease patients to treatment with glycosphingolipid synthesis inhibitorsmiglustat andeliglustat and ERT. Methods Seventeen GD1 patients were included (n = 6 eliglustat, (two switched from ERT), n = 9 miglustat (seven switchers), n = 4 ERT (median dose 60U/kg/m). Plasma protein markers reflecting disease burden (chitotriosidase, CCL18) and lipids reflecting substrate accumulation (glucosylsphingosine, glucosylceramide) were determined. Also, liver and spleen volumes, hemoglobin, platelets, and fat fraction were measured. Results In patients naïve to treatment, chitotriosidase, CCL18 and glucosylsphingosine decreased comparably upon eliglustat and ERT treatment, while the response to miglustat was less. After 2 years, median decrease of chitotriosidase was 89 % (range 77–98), 88 % (78–92) and 37 % (29–46) for eliglustat, ERT and miglustat naïve patients respectively; decrease of CCL18 was 73 % (63–78), 54 % (43–86), and 10 % (3–18); decrease of glucosylsphingosine was 86 % (78–93), 78 % (65–91), 48 % (46–50). Plasma glucosylceramide in eliglustat treated patients (n = 4) reached values below the normal range (n = 20 healthy controls). Biochemical markers decreased or stabilized in switchers from ERT to eliglustat (n = 2), but less in miglustat switchers (n = 7). Clinical parameters responded comparably upon eliglustat and ERT treatment. Conclusions Our explorative study provides evidence that biochemical markers respond comparably in patients receiving eliglustat treatment and ERT, while the corresponding response to miglustat treatment is less.